IMPLEMENTASI INOVASI TEKNOLOGI PERTANIAN DALAM MENDUKUNG PENINGKATAN PRODUKSI DAN PENGEMBANGAN TANAMAN UBIKAYU (Manihot esculenta L.) DI KOTA JAMBI - Widya Sari Murni; Edi Tando (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2022)
Cassava (Manihot esculenta L) is the main food besides rice and corn, has a strategic role as a food ingredient and industrial raw material as well as animal feed ingredients. The purpose of preparing this paper is to inform the implementation of agricultural technology innovations in supporting increased production and development of cassava plants in the city of Jambi. The results of the study show that Development of cassava in Jambi city has good prospects. There is support from the regional government in developing new areas that have the potential to increase production of cassava, food, feed ingredients and as an energy source. Implementation of innovations in cassava cultivation technology, inorganic and organic fertilization and grafting technology can increase cassava production.